CLINICAL COURSE OF SARS COV-2 INFECTION IN HOSPITALISED PREGNANT PATIENTS - Ansari, Asma; Siraj, Asifa; Khan, Sumaira; Akbar, Rabiya; Choudry, Abeera; Khalil, Hafsa (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine the clinical course and outcome of hospitalized pregnant patients with laboratory confirmed SARS CoV-2 (COVID-19) infection. Study Design: Prospective observational study. Place and Duration of Study: Obstetrics Unit of Pak Emirates Military Hospital (PEMH) and Combined Military Hospital (CMH) Rawalpindi, from May 2020 to Jun 2020. Methodology: All patients reporting for childbirth were tested for SARS CoV-2 and those testing positive were included. Demographic and reproductive profile including age, parity, occupation, contact and travel history, period of gestation at diagnosis and mode of delivery where applicable noted. The primary outcome was Virus clearance time and categorization according to severity of disease into asymptomatic, mild, moderate, severe and critical. Comparison was done between presence of co-morbid conditions and symptoms to category of COVID19. Neonatal sample evaluation for SARS CoV-2 was done. Results: Out of the 881 women giving birth 41 (4.6%) tested positive for SARS Cov-2. Majority were asymptomatic 28 (68.3%) followed by mild 08 (19.5%), moderate 04 (9.8%) and severe 01 (2.4%) category. There was significant association of COVID category with presence of symptoms (p-value <0.005) and comorbid (p-value <0.001). Mean virus clearance time was 8.2 ± 1.66 days. During hospital stay 34 (82.9%) delivered. All 34 (100%) of the delivered babies had no evidence of vertical transmission. Conclusion: Pregnant women with COVID-19 infection have nearly comparable clinical course to non-COVID women in this study. There is also no evidence of vertical transmission to the neonate.